SAT0156 The Flare-RA (Flare in Rheumatoid Arthritis) Questionnaire is Able to Detect Disease Activity Increase, I.E., Flare, Occurring between 2 Visits to the Rheumatologist:. (10th June 2014) - Morel, J.; Berthelot, J.M.; Constantin, A.; Debandt, M.; Gaudin, P.; Vittecoq, O.; Maillefert, J.F.; Meyer, O.; Pham, T.; Saraux, A.; Solau Gervais, E.; Spitz, E.; et al.
Abstract : Background: FLARE-RA (FLARE in Rheumatoid Arthritis) is a self-administered questionnaire developed to detect rheumatoid arthritis (RA) flare that has occurred in the meantime since the last visit to the physician 1 . The questionnaire is based on 11 items or statements exploring both RA patients and physician perceptions of RA flare in the 3-month period before the consultation to the rheumatologist. The respondents are asked to rate their agreement on a 0-10 numerical rating scale (NRS). FLARE-RA score is the mean of the 11 NRS. FLARE-RA has already been shown to be unidimensional, reliable and good correlation with disease activity at the time of questionnaire filling 2 . Objectives: To assess the ability of the FLARE self-administered questionnaire to identify past flare in RA patients. Methods: Study design was observational prospective 3-month study of patients with RA (satisfaction of 1987 ACR criteria, duration >6 months) and treated with stable doses of DMARDs. Patients were seen at baseline and 3 months (M3). To identify past RA flare, i.e., transient disease activity increase occurring in the 3-month period before the M3 visit, patients were asked to fill in the RAPID3 self-administered questionnaire 3 every week between baseline and M3. Spearman correlation coefficients were calculated to assess the association between the FLARE score at M3 and RAPID3-based past disease activity over the 3-month period between baseline and M3. The past disease activity was assessed by 3 different ways: area under the curve of RAPID3 scores (AUC), maximum RAPID3 value (MAX), and maximum delta of RAPID3 scores between 2 consecutive visits (DELTA MAX). The analysis was conducted in the whole population and in the subsample with low disease activity or remission at M3. Results: 132 patients were recruited from 13 centres: 78.7% women, 57.7 years old, 84.4% RF+, 78.7% ACPA+, DAS28 was 2.9, CRP was 5.7 mg/l and 81.2% had erosive disease. Complete RAPID3 data were available for 96, of whom 54 (56%) were in remission or low disease activity at M3 visit. Whatever the method used, FLARE-RA scores were significantly correlated with RA disease activity over the 3-month period preceding the visit to the rheumatologist. Conclusions: The FLARE-RA self-administered questionnaire can detect past RA flare and could represent a potential help to monitor disease activity between rheumatologist consultations and identify patients whose appointment should be anticipated or treatment revised References: Berthelot JM et al. Ann Rheum Dis 2012; 71(7): 1110-61. Morel J et al. Arthritis Rheum 2013; 65(10): S1231. Pincus T, et al. Rheumatology (Oxford) 2008; 47(3): 345-9. Acknowledgements: We thank Mrs Irawatti Lemonnier for coordination and management of the projet; Mrs Marie Line Epelding for stastistical analysis Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4614